Imperial spaces : placing the Irish and Scots in colonial Australia - Proudfoot, L. J. (Lindsay J.) (Studies in imperialism., 2011)
Imperial Spaces explores how the Irish and Scots imagined themselves within the landscapes of the Australian colonies. Using letters and diaries as well as records of collective activities, the book examines how the Irish and Scottish built new identities as settlers in the unknown spaces of Empire.